Chemerin-9 is neuroprotective in APP/PS1 transgenic mice by inhibiting NLRP3 inflammasome and promoting microglial clearance of Aβ - Jiawei Zhang; Yaxuan Zhang; Lan Liu; Mengyuan Zhang; Xiaojie Zhang; Jiangshan Deng; Fei Zhao; Qing Lin; Xue Zheng; Bing Fu; Yuwu Zhao; Xiuzhe Wang (Journal of Neuroinflammation)
Abstract Background Alzheimer’s disease (AD) is a prevalent neurodegenerative disorder worldwide, and microglia are thought to play a central role in neuroinflammatory events occurring in AD. Chemerin, an adipokine, has been implicated in inflammatory diseases and central nervous system disorders, yet its precise function on microglial response in AD remains unknown. Methods The APP/PS1 mice were treated with different dosages of chemerin-9 (30 and 60 µg/kg), a bioactive nonapeptide derived from chemerin, every other day for 8 weeks consecutively. The primary mouse microglia were stimulated by amyloid beta 42 (Aβ42) oligomers followed by treatment with chemerin-9 in vitro. ChemR23 inhibitor α-NETA was further used to investigate whether the effects of chemerin-9 were ChemR23-dependent. Results We found that the expression of chemerin and ChemR23 was increased in AD. Intriguingly, treatment with chemerin-9 significantly ameliorated Aβ deposition and cognitive impairment of the APP/PS1 mice, with decreased microglial proinflammatory activity and increased phagocytic activity. Similarly, chemerin-9-treated primary microglia showed increased phagocytic ability and decreased NLRP3 inflammasome activation. However, the ChemR23 inhibitor α-NETA abolished the neuroprotective microglial response of chemerin-9. Conclusions Collectively, our data demonstrate that chemerin-9 ameliorates cognitive deficits in APP/PS1 transgenic mice by boosting a neuroprotective microglial phenotype. Graphical Abstract